Analysis of the constitutional effectiveness of the right to education in times of the Covid-19 pandemic in Brazil (Research, Society and Development, 2022)
This study will address issues related to constitutional law regarding education in times of the Covid-19 pandemic in Brazil, in this context, this right is provided as a fundamental social right, where the State, the family and society are responsible to encourage and promote education, aiming at the full development of the citizen. In view of this perspective, this research aims to analyze the main problems caused by the pandemic situation that interfere in the guarantee of the right to education in the Brazilian territory, based on the difficulties faced by the most vulnerable portion of the population to have access to education and use the remote teaching modality, which became an option to ensure compliance with the 2020 school year. Methodologically, to carry out this research, the deductive method was adopted, which was carried out through the analysis of bibliographic data of a qualitative and documentary nature. From the results found, it is considered that the constitutional realization of the right to education was mitigated for the portion of the population that does not have the necessary conditions for the use of technologies to have access to remote education. Thus, due to the marked social and economic inequality that exists in the country, the poorest students are the most affected in terms of access to education during the pandemic period, mainly because this large portion does not have internet and access technologies for its use.